Diseño e implementación de una antena compacta para aplicaciones en internet de las cosas en 5G - Velin Sagbay, Jose David (2023)
In this research work, a two-port antenna has been developed and tested on a development board. The compact face-to-face antenna works in the industrial, medical, and free or known as ISM bands of 2.4 GHz and 5.8 GHz. The antenna has been developed for IoT applications for our current environment and considering the future development of telecommunications as a solution to mutual coupling for 5G bands. The antenna is constructed on a 1.5 mm wide FR-4 substrate with a dielectric permittivity of εr = 4.4 and a 0.035 mm copper coating. The total size of the antenna is 80x45 mm, with two octagon-shaped radiator elements attached to the ends with a triangular transmission line. The stub integration method was applied to compact the antenna and achieve the desired bands. In addition, a modified ground plane (DGS) was developed to improve the bandwidth and also helped to adjust the frequencies. To reduce mutual coupling in the 2.4 GHz band, a short-circuit line connecting the two radiating elements was used. The document is developed in 5 chapters. The first chapter presents the problem statement, the general objective, and the specific objectives to be achieved. The second chapter analyzes the state of the art and develops the theoretical framework. For the third chapter, the procedure used for the design and simulation of the structure is detailed. Subsequently, in chapter four, the results, measurements, characteristic mode analyses, and operation of the antenna are presented, as measured and implemented on the test board. Finally, chapter five presents the conclusions and recommendations reached with this research project